The distribution of the P-M hybrid dysgenesis system in Drosophila melanogaster strains from Brazil - Vetorazzi, VCR; Lourenco, M. F.; Carareto, CMA (Springer, 1999)
Wild-caught flies of Drosophila melanogaster from seven natural populations of extreme regions of Brazil (Sao Luis, MA; Teresina, PI; Rio Cipo, MG; Maringa, PR; Sao Jose do Rio Preto, SP; Joinville, SC; and Porto Alegre, RS) were studied with the purpose of evaluating hybrid dysgenesis due to mobilization of P elements and the regulatory capacity of the strains' cytotypes. Diagnostic crosses were made and the strains classified according to their P-M phenotypes. Four strains were classified as moderate P (MA, MG, PI, and SP), two as Q (PR and RS) and one as M' (SC). Females of southern strains (PR, SC, and RS) presented in A crosses lower degrees of gonadal dysgenesis scores than those from northern strains (MA and PI).
Keywords: hybrid dysgenesis; P-M system distribution; P element activity; P element susceptibility; Drosophila melanogaster